Successful tocilizumab therapy in seven patients with refractory adult-onset Still's disease. Issue 2 (3rd March 2016) - Bannai, Ei; Yamashita, Hiroyuki; Kaneko, Shunta; Ueda, Yo; Ozaki, Takashi; Tsuchiya, Haruka; Takahashi, Yuko; Kaneko, Hiroshi; Kano, Toshikazu; Mimori, Akio
Abstract : To evaluate the effects of tocilizumab (TCZ) on adult-onset Still's disease (AOSD), we reviewed medical records of seven patients with refractory AOSD treated with TCZ at our institution. TCZ therapy might allow rapid corticosteroid tapering and help maintain remission status, that is, resolution of clinical symptoms and normalization of biomarkers such as CRP and ferritin. Patients, however, should be monitored for the development of macrophage activation syndrome when TCZ is administered for active AOSD.